Artistic freedom in international law - Polymenopoulou, Eleni (Cambridge University Press, 2023)
"Lawyers interested in human rights, art law, cultural rights, cultural heritage law; artists and art students who want to know more about the legal framework applicable to arts ; free speech activists and human rights defenders; political scientists interested in global controversies such as Charlie Hebdo and the Danish Cartoons"--